LONGITUDINAL CHANGES IN PULMONARY FUNCTION ELUCIDATE GENES ASSOCIATED WITH AGE-RELATED PULMONARY DECLINE IN LLFS. (11th November 2018) - Wojczynski, M; Graham Barr, R; Zhang, Y; Thyagarajan, B; Perls, T; Christensen, K; Province, M A
Abstract: Pulmonary function (PF) is a key indicator of health in the elderly and the course of decline varies across individuals. Genetic loci that influence longitudinal changes in PF could provide biological insights into age-related decline and risk for age-related diseases. In LLFS, we characterized longitudinal changes in PF using statistical methods including regression and random coefficient modeling. Pulmonary outcomes (FEV1, FVC, FEV1/FVC) were modeled as a function of sex, age, height, weight, field center, and pack-years of smoking. Suggestive association results were detected on chromosomes 16 (FEV1), 19 (FVC), 6, 15, and 17 (FEV1/FVC). The suggestive signal on chromosome 16 is near DNAH3, TMEM159, and ZP2, all of which are genes known to have expression in lung tissue (GTEx). These are novel loci compared to known cross-sectional PF loci. Investigation into the mechanism of these genes is warranted to better understand age-related pulmonary decline.